Supply Chain Management in Service-based Firms: Empirical Study of Nigeria Telecommunication Sector - Ololade Elizabeth Obisesan; Olugbenga Ayo Ojubanire; Temitope Oluwagbenga Towolawi (International Journal of Supply Chain Management, 2022)
The study examined service supply chain management practices adopted by the Nigerian Telecommunication industry. It also evaluated the relationship between organizational performance and service supply chain management in the Nigerian Telecommunication Industry. A sample size of 368 respondents was selected using a simple random sampling technique. Data were analysed using descriptive and inferential statistics - regression analysis. Results from the study showed that customer relationship, strategic supplier partnership, quality of information sharing, and extent of outsourcing were the supply chain management practices adopted by the telecommunication companies. Also, certain financial performance such as market share, adjusted operating profit, revenue, and related organic growth was the highest. Finally, results showed that strategic supplier partnership and customer relationship all had a significant and positive influence on organizational performance, while the quality of information sharing, the extent of outsourcing, and postponement all had no significant influence on the performance of the organization. The contribution of this study is that it expounds on the existent supply chain methodologies from a service-based enterprise perspective with empirical validation. While extant studies have focused majorly on supply chain issues in manufacturing enterprises, this study examined the concept in the service industry of an emerging market.